Effects of Subchronic Exposure to Cadmium and Diazinon on Testis and Epididymis in Rats. (7th December 2014) - Adamkovicova, Maria; Toman, Robert; Cabaj, Michal; Massanyi, Peter; Martiniakova, Monika; Omelka, Radoslav; Krajcovicova, Vladimira; Duranova, Hana
Abstract : The present study aimed to elucidate the structural changes in testis and epididymis of adult rats following subchronic peroral administration of cadmium at 30 mg/L, diazinon at 40 mg/L, cadmium at 30 mg/L, and diazinon at 40 mg/L, respectively. At the end of 90-day experiment, the samples of the testes and epididymis were assayed by qualitative and quantitative histological methods. The testis and epididymis weights increased following exposure to cadmium and simultaneous exposure to cadmium and diazinon. Testicular damage following cadmium and diazinon coexposure was significantly less expressive than in groups with individual administration of these compounds. Cadmium caused a significant thickening of seminiferous epithelium, cellular degeneration, and necrosis. Desquamation of immature germ cells resulted in a significant increase of intraepithelial spaces and reduced tubule volume in all experimental groups. Vascular dilation and congestion were detected in the interstitial tissue. The changes in epididymal histology in the group exposed to cadmium and group exposed simultaneously included a reduction of epithelium, necrotic epithelial cells, vasoconstriction, and interstitial edema together with mononuclear cell infiltration. Results did not indicate a synergistic or any additional effect from the simultaneous administration of both toxicants. Further research is needed to determine the significance and the mechanism of the adverse effects.